Sosialisasi & Pelatihan PeningkatanPartisipasi Politik Pelajar sebagai Pemilih Pemula di SMK Muhammadiyah 7 Purwoharjo Banyuwangi - Baktiawan Nusanto; Dodik Aris Setiawan (Jurnal Pengabdian Masyarakat, 2026)
The level of political participation among first-time voters in Indonesia is still relatively lowand is often not supported by an adequate understanding of the politicalprocess and democracy. This condition is also found among students at SMK Muhammadiyah 7 Purwoharjo Banyuwangi, most of whom have not received targeted political education, even though they have great potential in determining the direction of regional development in the future. Therefore,a programme to strengthen political literacy is needed to increasethe awareness, involvement, and responsibility of students as first-time voters. The objectives of this community service activity are to increase political understanding, active participation in simulated democratic processes, and to foster a critical and caring attitude towards regional development. Students are expected not only to understand the government system and political institutions, but also to be able to participate rationally in public decision-making processes. The implementation methods include interactive digital media-based political education outreach, focus group discussions (FGD) on regional development issues, as well as election simulations and the role of state institutions. The expected outcomes are: an increase in students' political understanding of at least 70%, active participation of at least 85% of participants in the entire series of activities, and the development of political education media in the form of digital modules and socialisation videos. This programme is expected to become a model for practical political educationin schools so that it can foster a young generation that is politically savvy, tolerant, and actively contributes to the development of the Banyuwangi region.